Sharia Investment Socialization Through Instagram Social Media - Budiarti, Dian; Munawaroh; Prihatini, Hani (FEBI UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to provide socialization of sharia investment and analyze the effectiveness of socialization carried out through Instagram social media. This study uses data that comes from various related issues discussed. The references taken are books that discuss the problem, articles or scientific journals obtained from soft files or hard file books and also through information technology or the internet. This research is also included in qualitative research using the literature study writing method. kinds of studies, namely descriptive studies and constructive analysis. Descriptive studies are carried out by identifying various findings, which are then presented based on these findings in a structured and systematic manner. In this case, identifying the various outreach and education programs that have been carried out. This research also examines constructively analytically, namely armed with various findings that exist in various socialization and education. The results of the study show that the enthusiasm of Instagram users in listening to the discussion videos that have been made by the author and is believed to be very useful for those who are about to start investing or for those who are already investing and want to switch to investments that are good according to their religion, or maintain their mandated financial trust in investment instruments.